Improving social presence in online higher education: Using live virtual classroom to confront learning challenges during COVID-19 pandemic - Aldosari, Aljawharah M.; Alramthi, Saad M.; Eid, Hala F. (Frontiers in Psychology, 2022)
The COVID-19 pandemic has compelled practically all higher education institutions to adopt online education tools over the previous two years. Online education has a huge potential to supplement or take the place of in-person instruction. However, there are certain drawbacks of online learning, such as the absence of classroom environment interaction and the difficulty in keeping track of students' engagement and participation. In this study, a live virtual classroom was developed to aid students in their learning activities. The effectiveness of this live video classes was reported from both students and instructors, as well as the variables promoting their implementation within higher education institutions. One of the more significant findings to emerge from this study is that the instructors found it convenient, as they could readily check course participants understanding by studying their live video lectures. The second major finding was that students felt satisfaction with online learning while asking questions without interfering with the instructor's presentation. Moreover, peers could also provide them with more expertise. However, the teaching process became dynamic, requiring the educator to pay close attention. The course participants also experienced anxiety when they were in front of other people. Additionally, both the instructor and the students need to be highly self-sufficient in technology